2019
DOI: 10.1007/s13201-019-1112-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of trapezoidal sharp-crested side weir discharge coefficients under subcritical flow regimes using CFD

Abstract: Side weirs are utilized to regulate water surface and to control discharge and water elevation in rivers and channels. Here, the discharge coefficient for trapezoidal sharp-crested side weirs (TSCSW) and their affecting parameters are numerically investigated. To simulate the hydraulic and geometric characteristics of TSCSWs, three weir crest lengths of 15 cm, 20 cm and 30 cm with lengths of 20 cm, 30 cm and 40 cm and with two different sidewall slopes are utilized. The results show that for constant P/B (P: w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The RNG k-ε model improves the standard k-ε model (Equations ( 12) and ( 13)), reflecting small-scale effects by large-scale motion and modified viscosity terms, and can handle the flow with a large degree of curvature well [39]. This model showed satisfactory outcomes in previous studies on hydraulic engineering studies in complex geometry and flow fields [26,27,[40][41][42][43][44][45][46].…”
Section: Turbulence Modelmentioning
confidence: 78%
“…The RNG k-ε model improves the standard k-ε model (Equations ( 12) and ( 13)), reflecting small-scale effects by large-scale motion and modified viscosity terms, and can handle the flow with a large degree of curvature well [39]. This model showed satisfactory outcomes in previous studies on hydraulic engineering studies in complex geometry and flow fields [26,27,[40][41][42][43][44][45][46].…”
Section: Turbulence Modelmentioning
confidence: 78%
“…They indicated that nappe breakers placed on the trapezoidal labyrinth weirs and circular labyrinth weirs reduced the discharge coefficient by up to 4% compared to an un-amended weir. Numerical methods have been used by various researchers in recent decades [12][13][14][15][16][17]. Shaghaghian and Sharifi [18] investigated the characteristics of flow in triangular labyrinth weirs using FLUENT.…”
Section: Figure 1 -Labyrinth Weir In a Channel With Converging Wallsmentioning
confidence: 99%
“…FLOW-3D ® is a general purpose computational fluid dynamics (CFD) program for modeling a wide variety of fluid flow fluid flow problems [13,20]. It uses the finite volume method to solve the RANS equations (Reynolds Average Navier-Stokes) in a Cartesian, staggered grid.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Here, the Renormalization Group (RNG) k-ε turbulence model was selected. This model has been applied to similar flow scenarios and is capable of providing accurate and efficient solutions [34][35][36][37][38]. The RNG k-ε model equations are given by:…”
Section: Numerical Modelmentioning
confidence: 99%